(untitled) (Research, Society and Development, 2020)
Context: The rapid growth of the elderly population in the world, due to the increase in longevity and aging, indicates the need to implement measures to guarantee this population a better quality of life. The prospect of a new and fast digital society is part of the daily lives of these elderly people, many of whom have not yet been included in digital social networks. Objective: To verify if there are effects of a digital inclusion program on the quality of life of the elderly. Methodology: Application of an intervention protocol with 44 elderly participants, where 21 were submitted to a digital inclusion protocol - group called experiment (GE), for two months, with 10 2-hour meetings and, 2 control groups, one with activities (GCA) not related to information technology, and another without activities (GSA). To assess the effects of this digital inclusion, pre and post intervention instruments were applied. Instruments used: Socio-demographic questionnaire, ABEP Brazil Criteria economic questionnaire, WHOQOL-BREF and WHOQOL-OLD. Conclusion: no statistically significant and proven differences were found to affirm any effects of digital inclusion on the quality of life of the elderly.